Symbolization, convention, identity: an analysis of the functional and semantic trinity in the focus of comparative studies (Journal of Philosophy Culture and Political Science, 2025)
Taking into account comparative studies, the article provides a consistent and original analysis of symbolization, convention and identity as an integral, internally interrelated problem. Symbolization is considered as a conceptual and methodological basis of research. Its relevance is substantiated. A meaningful disclosure of the symbol is given. In connection with this, the substantiation and definition of the concept of convention as a special form of socio-cultural predestination of a symbol, as a resultant factor of ethnocultural originality and civilizational difference is given. Next, the connection of symbolization with the phenomenon of identity is updated. His conceptual and semantic analysis is given from the perspective of ethnicity. The peculiarities of the national identity of the Mongolian ethnic group of Russia, the Buryats, are revealed. All this is reflected on the basis of a comparative approach (China, Japan, Korea, Mongolian ethnic groups).Keywords: symbol, convention, code, comparative studies, ethnicity, culture, language, national identity, Mongolian ethnicity, Buryats.